2021
DOI: 10.4103/jfmpc.jfmpc_1500_20
|View full text |Cite
|
Sign up to set email alerts
|

Parental knowledge and practices toward foreign body aspiration in children in the Al Qassim region of Saudi Arabia

Abstract: Background: Foreign body aspiration (FBA) is a perilous condition with a high mortality rate, especially in children less than three years of age. Aim: This study aimed to assess parental knowledge and practices toward FBA in children in the Al Qassim region of Saudi Arabia. Materials and Methods: This is a descriptive cross-sectional study conducted among Saudi parents at AlQassim region, Saudi Arabia during the period between February 2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 17 publications
8
17
5
Order By: Relevance
“…(2021) (50) The results were also congruent with Almutairi and Alharbi (2021) (51) which displayed that the mean and standard deviation knowledge score was 4.99 (1.44)/9 opinions and the practice score was 12.6 (2.15)/21 opinions. Fathers and mothers were more than half and Fathers and mothers with good knowledge were more than one third also, fathers and mothers with poor practices were 55.6% and fathers and mothers with good practices 44.9%.…”
Section: Discussionsupporting
confidence: 78%
“…(2021) (50) The results were also congruent with Almutairi and Alharbi (2021) (51) which displayed that the mean and standard deviation knowledge score was 4.99 (1.44)/9 opinions and the practice score was 12.6 (2.15)/21 opinions. Fathers and mothers were more than half and Fathers and mothers with good knowledge were more than one third also, fathers and mothers with poor practices were 55.6% and fathers and mothers with good practices 44.9%.…”
Section: Discussionsupporting
confidence: 78%
“…In a similar study done in Medina in Saudi Arabia the majority of parents (43.3%) were aged 31 -40 years followed by 40.4% aged 20 -30 years [10]. region showed that the majority of parents have bachelor degree or diploma representing 73% in one study [11] and 59.2% in another study [12]. The increased level of education positively impacts the knowledge and attitude of parents toward childhood vaccination.…”
Section: Demographic Variables Of the Studymentioning
confidence: 78%
“…We used a validated assessment tool employed in a previous study [4]. The questionnaire was translated into Arabic.…”
Section: Study Toolmentioning
confidence: 99%
“…FBA has a variable clinical presentation ranging from being asymptomatic to severe respiratory distress and death [3]. Parents witnessing and reporting the incident of inhalation to a physician is helpful for early diagnosis and intervention [4,5]. Furthermore, the late diagnosis of FBA can be associated with a high rate of mortality and morbidity [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation